Comparison of Respiratory Symptoms among Under Five Children Living in Households Using Biomass Fuel and Fossil Fuel in An Urban Area of Bangladesh (Community Based Medical Journal, 2023)
A cross-sectional study was conducted at Uttarkhan Thana under Dhaka City Corporation, Bangladesh, between January and December of 2018, to compare respiratory symptoms in under five children living in households using biomass fuels and fossil fuels. The study community comprised of three areas named Vatulia, Munda and Pulartek of Ward No. 4 of Uttarkhan Thana. Total number of households were 1329. Population size in total was 5114, where 2548 were male and 2566 were female. Among them 200 households were chosen by simple random sampling technique – selected households had under five children and met the inclusion criteria (i.e., mother or caregiver of children under five years of age wanted to participate voluntarily. However, we excluded children having congenital anomalies and households using electricity for cooking purpose. A semi-structured questionnaire was used as data collection instrument. Questionnaire included socio-demographic characteristics such as age, sex, educational status, marital status, occupation, number of family members. Cooking related information, e.g., frequency of cooking, duration of cooking, type of fuel used, presence of children during cooking, sleeping in the kitchen and respiratory symptoms in children, e.g., nasal discharge, cough, breathing problems, chest tightness, wheezing, and sore throat were included in the data sheet. Besides, it contained information regarding location of the kitchen, area of the kitchen and presence of any ventilation facility and chimney. Nasal discharge (79.7% vs. 71.6%), cough (69.9% vs. 64.2%), and sore throat (9% vs. 6%) were more common in biomass fuel users’ children. In contrast, shortness of breath (22.4% vs. 18.8%) and wheezing (31.3% vs. 24.1%) were more common among fossil fuel users’ children. However, none of those differences were statistically significant (P>0.05).CBMJ 2023 July: vol. 12 no. 02 P: 164-170